Effect of transformational leadership and compensation on employee performance - Diantari, Ni Putu Astrimita; Riana, I Gede (International research journal of management, IT and social sciences, 2019)
A leader is a person who has the skills and strengths so as to be able to influence others to carry out certain activities, for the achievement of goals. This study aims to analyze the effect of compensation and transformational leadership on employee performance. Using a sample of 76 employees at PT. Raditya Perkasa, this study used a questionnaire as the main instrument. The collected data were analyzed using multiple linear regression using SPSS 20. The results showed that compensation and transformational leadership had a significant positive effect on employee performance. Partially, this study found that transformational leadership has a stronger effect on employee performance compared to compensation. Furthermore, the values ??of transformational leadership are considered very important in supporting employee performance. Transformational leadership includes two essential elements, namely relational and dealing with real change so that leaders and followers raise themselves to each other to arrive at certain levels of motivation and performance.